Leading Change at The Faculty of Education in Light of Kotter's Change Model - Onia, Saifaldin Idris (JURNAL AL-TANZIM, 2022)
The purpose of this study was to examine Kotter's leading change model at the Faculty of Education University of Khartoum with a major purpose of evaluating the contribution of this theory to enhance the importance and understanding of leading change at the University context. In doing so, a survey research design was employed. Among 239 staff members at the Faculty of Education University of Khartoum, data were collected from 106 (44.00%) respondents using questionnaire. Data collected were analyzed using one sample t-test. The result showed that creating a climate for change has been practised in the Faculty of Education University of Khartoum. The Faculty of Education University of Khartoum has engaged and enabled the whole organization in the change process. The findings also indicated that the Faculty of Education University of Khartoum has implemented and sustained change process. Hence, the implication of these findings adds to the understanding of how college officials ought to play a role model in embedding the change in their behaviors.